2014
DOI: 10.1007/s00348-014-1708-6
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian measurements of the fast evaporation of falling diethyl ether droplets using in-line digital holography and a high-speed camera

Abstract: measurements of the fast evaporation of falling diethyl ether droplets using in-line digital holography and a high-speed camera. Experiments in Fluids, Springer Verlag (Germany), 2014, 55, 1708 (13 p.). 10.1007/s00348-014-1708-6. ujm-01020697 Experiments in Fluids manuscript No. (will be inserted by the editor) Lagrangian measurements of the fast evaporation of falling Diethyl Ether droplets using in-line digital holography and a high-speed camera Abstract The evaporation of falling Diethyl Ether droplets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Typical evaporation rate measured along trajectories are presented. While without turbulence this evaporation rate is close to that predicted by the standard "d 2 " law (Marié et al, 2014), it may significantly fluctuate and deviate from this law in presence of turbulence. The thermal-vapor concentration boundary layers and wakes visible around each hologram of droplets have also been reconstructed with a standard back propagation method, providing a convincing picture of the vapor film around the droplet.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Typical evaporation rate measured along trajectories are presented. While without turbulence this evaporation rate is close to that predicted by the standard "d 2 " law (Marié et al, 2014), it may significantly fluctuate and deviate from this law in presence of turbulence. The thermal-vapor concentration boundary layers and wakes visible around each hologram of droplets have also been reconstructed with a standard back propagation method, providing a convincing picture of the vapor film around the droplet.…”
Section: Introductionmentioning
confidence: 76%
“…It is caused by the deflection of the light by the refractive index gradient in the thermal -vapor concentration boundary layers and wakes developing around the droplet as discussed in Seifi et al (2013); Méès et al (2013). It was shown that the wake image visualizes well the Lagrangian relative motion of the air around the droplet (Chareyron et al, 2012;Marié et al, 2014). The effect of the vapor is more pronounced in the center part of the hologram and is not taken into account in the hologram Fraunhofer formation model.…”
Section: D Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations